EFEKTIVITAS PEMBELAJARAN DARING DENGAN MENGGUNAKAN MEDIA ONLINE GOOGLE CLASSROOM (GCR) PADA MATA KULIAH KAJIAN KURIKULUM BAHASA INDONESIA MAHASISWA PGSD - Purba, Nancy Angelia; Simaremare, Juni Agus (Unversitas Katolik Santo Thomas, 2022)
This study aims to describe the effectiveness of online learning using Google Class Room (GCR) online media during the COVID-19 pandemic for Indonesian language curriculum studies. This research is a descriptive quantitative research using online media, namely google form. The research population was all sixth semester students of PGSD using random sampling technique by considering population homogeneity. The data collection instrument used an online learning questionnaire. Data analysis used descriptive statistics. The results of the study illustrate that students assess learning in Indonesian language curriculum studies using GCR online media, namely students assess learning Indonesian language curriculum studies using effective online media (60%), most of them (37%) are average and very effective ( 3%). Finally, to improve the quality of learning for Indonesian language curriculum studies during the COVID-19 pandemic, lecturers must comply with suggestions from respondents, namely implementing new strategies, conducting more discussions, providing concise and easy-to-understand material and adding more videos. interesting again.